Dissolving microneedles for melanoma: Most recent updates, challenges, and future perspectives - Hussain, Yaseen; You, Ben Gang; Huang, Linyu; Liu, Xiaoyin; Dormocara, Amos; Shah, Kiramat Ali; Ali, Tariq; Cao, Qing Ri; Lee, Beom Jin; Elbehairi, Serag Eldin I.; Iqbal, Haroon; Cui, Jing Hao (International Journal of Pharmaceutics, 2025)
Skin cancer is one among the common types of cancers, affecting millions of individual globally. The conventional anticancer therapy such as chemotherapy results in worst systemic and local side effects as well as inhibit the growth of healthy cells around the tumor cells. Dissolving microneedles (DMNs) is a groundbreaking technology with less invasive and more targeted features. Physically, these tiny dissolving needles deliver the anticancer payloads drug to the tumor site after its direct application on the skin surface. Specifically, the DMNs release the anticancer drug cargoes into the cancerous cell sparing the healthy cells around the tumor, thus has provided a significant contribution in the landscape of traditional skin cancer therapy. This targeted therapeutic approach of dissolving microneedles shows a significant therapeutic outcome in decreasing the growth of cancer cells in pre-clinical studies. Dissolving microneedles (DMNs) have demonstrated effectiveness in the targeted delivery of drugs, genes, and vaccines specifically at the site of skin tumors. This method mimics the localized release of adjuvants and immunomodulators, leading to significant humoral and cellular immune responses that are beneficial for skin cancer therapy. In this review, the current trends and potential roles of dissolving microneedles in delivering therapeutic agents focused on treating skin melanoma have been highlighted, drawing insights from recent literature. This emphasizes the promising applications of DMNs in enhancing treatment outcomes for skin cancer patients. Lastly, future perspectives were identified for improving the therapeutic potential and translation of DMNs into clinic.
Keywords: Administration, Cutaneous; Animals; Antineoplastic Agents; Drug Delivery Systems; Humans; Melanoma; Microinjections; Needles; Skin Neoplasms; Dissolving microneedles; Melanoma; Transdermal drug delivery